Cover Picture: Freezing the Bioactive Conformation to Boost Potency: The Identification of BAY 85‐8501, a Selective and Potent Inhibitor of Human Neutrophil Elastase for Pulmonary Diseases (ChemMedChem 7/2015). Issue 7 (July 2015) - von Nussbaum, Franz; Li, Volkhart M.‐J.; Allerheiligen, Swen; Anlauf, Sonja; Bärfacker, Lars; Bechem, Martin; Delbeck, Martina; Fitzgerald, Mary F.; Gerisch, Michael; Gielen‐Haertwig, Heike; Haning, Helmut; Karthaus, Dagmar; et al.
<x xml:space="preserve">Abstract</x> The front cover picture shows the inhibitor (4S)‐4‐[4‐cyano‐2‐(methylsulfonyl)phenyl]‐6‐methyl‐2‐oxo‐1‐[3‐(trifluoromethyl)phenyl]‐1, 2, 3, 4‐tetrahydropyrimidine‐5‐carbonitrile in complex with human neutrophil elastase (HNE), a key target for the potential treatment of pulmonary conditions due to its high activity in inflammatory diseases. Inhibition of HNE is expected to re‐establish protease balance in disease settings with elevated levels of HNE. A novel class of dihydropyrimidinone lead compounds was identified and optimized to give orally active compounds with favorable pharmacokinetics such as the chemical probe BAY‐678. Without compromising the excellent target selectivity of these lead compounds, picomolar potency was achieved by 'freezing' their structure in the bioactive conformation. Specifically, the methyl sulfone substituent was strategically positioned to accomplish optimal interaction with the S2 pocket of HNE. The clinical candidate, BAY 85‐8501, exhibited efficacy in a rodent model of acute lung injury and is currently being tested for the treatment of pulmonary diseases. For further details, see the Full Paper by Franz von Nussbaum, Volkhart M.‐J. Li et al. on p. 1163 ff.